Interlayer‐Engineering and Surface‐Substituting Manganese‐Based Self‐Evolution for High‐Performance Potassium Cathode. Issue 1 (10th November 2022) - Caixiang, Zhuoma; Hao, Jiaxin; Zhou, Jiang; Yu, Xinzhi; Lu, Bingan
Abstract: Manganese‐based layered oxides cathodes have attracted enormous interest due to their advantages in cost and energy density. The significant challenges of Mn‐based layered oxides for potassium‐ion batteries (PIBs) are complex phase transition and Mn dissolution upon K + intercalation/deintercalation. Here, a P3‐type K0.45 Rb0.05 Mn0.85 Mg0.15 O2 (KRMMO) cathode material is proposed to address the above challenges. The results show that rubidium acts as a pillar to expand interlayer spacing and stabilize the structure, while magnesium partially replaces Mn to suppress the Jahn–Teller distortion of the Mn 3+ . The KRMMO cathode exhibits high capacity of 108.0 and 77.3 mAh g −1 at 20 and 500 mA g −1, respectively, and retains 98.2% of its initial capacity after 200 cycles. Compared with P3‐K0.5 MnO2, the capacity fading of P3‐KRMMO is effectively suppressed, which is mainly due to the synergistic contribution of Rb and Mg ions in the alleviation of volume change and suppression of phase transition. This work may open a new avenue for the design and optimization of layered cathode materials for PIBs and beyond. Abstract : This work reports a phase‐change‐free K0.45 Rb0.05 Mn0.85 Mg0.15 O2 (KRMMO) cathode with Rb and Mg substituted for potassium‐ion batteries. In situ characterizations show that the dual stabilization effect of Rb and Mg effectively suppresses the phase transition and alleviates the structural volume change. The electrochemical performance of KRMMO cathode exhibits high capacity and remarkable stability.